EDUKASI DAN PENDAMPINGAN MASYARAKAT TENTANG PENGOLAHAN SAMPAH MENJADI BARANG BERNILAI - Sahrul Hidayatulloh; Dani, Baiq Onteng Purwe; Rizkyantara, Eky; Litah, Popyn Nur; Mariadi, Maliki; Sari, Sasmita; Putri, Ade Iasyah; Pratama, Lalu Aditya Artha; Munawarah, Jannatul; Kusmala, ilvia Sri; Atsar, Abdul (Jurnal Wicara, 2025)
Lantan Village is located in Batukliang Utara District, Central Lombok Regency, West Nusa Tenggara Province. The village covers an area of approximately 5,777.05 hectares and consists of ten hamlets. Lantan Village is one of the tourist villages with highly attractive tourism potential, including waterfalls, an international motocross circuit, and a camping ground. This study aims to enhance the understanding and skills of the community in processing waste into valuable products while preventing environmental pollution caused by unmanaged waste. This, in turn, will create a clean, healthy, and comfortable environment. This research employs a qualitative approach with a case study method. The subjects of this study are the residents of Lantan Village. The results of this socialization activity are expected to increase the creativity, knowledge, and awareness of the community regarding waste management, turning waste into valuable products. This effort can contribute to the community's welfare by improving the local economy while minimizing waste accumulation to maintain the village’s environment. In conclusion, the waste management socialization program in Lantan Village has successfully raised awareness and improved the skills of the community in independently managing waste. By transforming waste into economically valuable products, this program has had a positive impact on environmental, social, and economic aspects.